Cardio-oncology organization patterns in Italy: one size does not fit all. Issue 5 (May 2018) - Canale, Maria Laura; Lestuzzi, Chiara; Bisceglia, Irma; Vallerio, Paola; Parrini, Iris
Abstract : Aims: Cardio-oncology is imposing as the specialty deputed to the management of a large and rapidly increasing population of cancer patients receiving anticancer treatments with cardiovascular side effects or presenting with cardiac and oncological comorbidities. Organization patterns dramatically vary across Italy. Methods: On the behalf of ANMCO, we have analyzed the characteristics of cardio-oncology services across different hospital types in Italy. A questionnaire was sent out to all ANMCO divisions inquiring about inner organization, workload, multidisciplinary team and inter-hospital connections. Results: Ninety-eight centers sent back the questionnaire. We summarize different paths into four reference assistance models (sizes XL, L, M and S) according to hospital characteristics, cardio-oncology population size, specialists availability, local facilities and the hospital-surrounding network. We define sizes of the proposed pathways highlighting the need to tailor the model in each single situation. Conclusion: No single cardio-oncology organization model can be applied to all hospitals. Each center could select the size/model that best fits its organization. Multidisciplinarity and networking play a crucial role.